PENATAAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA (PKL) DI KECAMATAN TUALANG PERAWANG KABUPATEN SIAK TAHUN 2013 - ", Kasrimadi; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In an effort to improve the city's image as a clean Siak beautiful, orderly and comfortable then demanded an active role of government as a policy maker, the necessary regulations concerning the structuring and empowering Local street vendors (PKL), this refers to the rules that have been set by the central government the Minister of Affairs of the Republic of Indonesia Number 41 Year 2012 on Guidelines for Planning and Empowerment Street Vendors, Planning and Empowerment is the make the determination, removal, demolition and removal of street vendors by taking into account the location of the public interest, social, aesthetic, health, economy, security, order, cleanliness environment and in accordance with legislation. And as pedomanya Regional Regulation (Government) Siak District No. 12 of 2007 on Structuring and Empowerment street vendors (PKL) the Empowerment of Arrangement has yet to be implemented by the government in 2013 District of Tualang Perawang. This study was conducted in order to find out about the arrangement and the Empowerment of Street Vendors in the District Tualang Perawang Siak, and determines the factors that inhibit Planning and Empowerment Street Vendors in the District Tualang Perawang, Location of the study was conducted in the District, the Department of Market UPTD, and SATPOL PP.Jenis this research is descriptive qualitative research method. The nature of this research is a case study.The results of this study indicate that the policy of restructuring and empowerment of street vendors (PKL) in District Tualang Perawang not been successful, due to various factors ie, traders feel less clear on the policies made by the sub-district government Tualang Perawang, trades do not want to be moved because of the new place is managed by investor, price shanties place burdensome new allocation street vendors (PKL), shortage of funds, the allocation of new places away from the crowds of the population, the presence of weak enforcement interest groups conducted by the Civil Service Policen Unit (SATPOL PP)Keywords: Strukturing, Empowerment, Street Vendors (PKL)